PERAN DINAS PENDIDIKAN DALAM PERUMUSAN PELAKSANAAN PENCEGAHAN ANAK RAWAN PUTUS SEKOLAH DI KOTA PEKANBARU TAHUN 2013 – 2015 - Fani Fitriani; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The role of the education office is the supervisors, controllers, administrators and supervisors of primary and secondary education for the realization of national education. As for the function of education that is as a tool to free people from ignorance, oppression, backwardness and poverty that hit the Indonesian society.The purpose of this study is to : (1) Know the role of the education office in the prevention of children prone to drop out; (2) Know what are the causes of still children who drop out of school. This research uses qualitative research method with descriptive research type, which can be interpreted as problem solving process which is investigated by describing the state of research subject based on facts that appear during the research which then continued with based on the existing theories. Data analysis is done by data reduction, data presentation, and conclusion or verification.Based on the results of this study concluded that with the role of the Education Office then the level of public participation in the importance of education activities in Pekanbaru City will increase. But the fact that the participation of the community on the lack of education is caused by several factors,namely the low interest of children to go to school, the size of brothers, economic factors, social factors, peer factors and others. As for the factors that will cause the existence of children who drop out of school is the misuse of budget allocations, and lack of extension in remote areas.Keywords: Role, Education Authorities, Drop Out